Pengaruh Perbedaan Jenis Pasir terhadap Properties Material dan Kuat Tekan Beton - Tendy Arizki; Tira Roesdiana (Institut Teknologi Garut, 2026)
Fine aggregate plays a significant role in concrete mixtures because it constitutes approximately 60–75 percent of the total volume, meaning that its characteristics directly influence concrete quality. In the Ciayumajakuning region, Cimalaka sand (Sumedang) is more commonly used even though its logistical distance is farther compared to Ciputat sand (Indramayu); however, no scientific study has directly compared the two materials. This study aims to examine the material properties characteristics and the effect of using these two types of sand on the compressive strength of concrete with a design strength of f'c 25 MPa, as well as to assess the feasibility of Ciputat sand as a substitute for Cimalaka sand. The method applied was experimental using 24 cylindrical specimens measuring 15 cm × 30 cm, tested at the ages of 7, 14, 21, and 28 days in accordance with SNI 03-2834-2000. The material property test results indicate that Ciputat sand belongs to Zone 3 with a mud content of 3.0 percent (meeting the SNI requirement of =< 5 percent), while Cimalaka sand belongs to Zone 1 with a mud content of 7.28 percent (exceeding the SNI limit and therefore requiring washing). At 28 days, the average compressive strength values of the concrete were recorded at 26.138 MPa for Ciputat sand and 25.666 MPa for Cimalaka sand, both exceeding the target design strength of f'c 25 MPa. The insignificant difference in values indicates that the performance of both sands is relatively equivalent, suggesting that Ciputat sand has the potential to be used as a more logistically efficient alternative without compromising structural quality.